The impacts of electric vehicles uptake and heat pump installation on the Irish economy - Kelly C. De Bruin; Aykut Mert Yakut (The Economic and Social Research Institute (ESRI), 2021)
This paper examines the economic and environmental impacts of the adoption path of electric vehicles (EVs) and home retrofitting in the form of heat pumps (HPs) projected in the recent Climate Action Plan (CAP21) for Ireland. This analysis assumes the level of carbon tax follows the path committed by the Irish government in June 2020 and in the CAP21; reaching C100 per tonne of CO2 in 2030 and includes a government subsidy for HPs. The results show that an increase in the carbon tax has substantial impacts on emission reduction, and EV adoption and HP installations can further reduce emissions but to a lesser degree than the carbon tax increase. Compared to a carbon tax alone, the wide-scale adoption of EVs and HPs boost the economy and employment. This boost leads to a rebound effect, where emissions increase slightly in other sectors of the economy. The results prove the importance of simultaneous use of carbon taxation and electrification of transport and home heating, where carbon taxation increases the benefits of adopting low carbon technologies and adoption reduces the costs of carbon taxation.
Keywords: 330; Elektrofahrzeug; Wärmepumpe; Ökosteuer; Umweltverträglichkeit; Wirkungsanalyse; Treibhausgas-Emissionen; Irland